Corporate Social Responsibility: Issues and Challenges in India - Tandon, Dinesh; Singh, Harpreet; Bawa, Jagmeet (Gyan Management Journal, 2016)
The concept of corporate social responsibility has been tremendously gaining acceptance in India. The corporate have started integrating the concept in every function of their business activities, like marketing, finance, human resource management etc. The social responsibility is now no more a secoridary part of an entity but a business idea. The business houses have realised that the development and growth is possible in entirety not in individuality. Equality and participation for upliftment of the society to the heights of modern, sustainable world is the need of the hours. An attempt has been made in this paper to deeply understand the corporate social responsibility in India. The paper suggests that integration of corporate social responsibility with overall operations of business is the way to improve its impact and bring effectiveness.
Keywords: Corporate Social Responsibility; Challenges of CSR